The Effect of Entrepreneurial Orientation on Social Performance and Financial Performance of Small and Micro Food Business Actors in West Jakarta Area Mediated by Open Innovation - Dodi Cristiawana; Hutabarat, Zoel (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Micro, Small and Medium Enterprises (MSMEs) continue to experience growth and development to this day. In 2022, there will be 65 million MSMEs in Indonesia, which accounts for 99% of all business units in the country. MSMEs play a crucial role in supporting the national economy, especially in facing the threat of recession, and are the backbone of the country's economy. The growth of MSMEs has a positive impact on the economy both macro and micro in Indonesia. Micro and small businesses also have an important role in the economic movement of DKI Jakarta. Micro and small businesses are still categorized as businesses with low productivity and technology use. Although they have begun to have the ability to innovate and develop technology. However, micro and small businesses are still constrained by a number of problems such as access to capital, raw materials, limited employee training, social responsibility and partnerships. The purpose of this study is to see the effect of entrepreneurial orientation on financial performance and social performance mediated by open innovation in micro and small food business actors in the West Jakarta city area. The number of samples used in this study was 210 micro and small food business actors. The data obtained will be processed using PLS-SEM version 4.0.